Ukraine administrative and legal regulation of education for persons with disability - Talanchuk, Iryna (Social Welfare: Interdisciplinary Approach, 2015)
Education of people with disabilities as the object of administrative and legal regulation of public policy in Ukraine is analyzed in the article. It is stated that the society has passed a difficult path in its attitude to the people with disabilities - from aggressive rejection to realization of the need for their integration into the community. In the present conditions, the urgency of developing and implementing measures for professional training of all able-bodied and disabled people who want to work with the aim of integration them into society is proved.